1996
DOI: 10.1104/pp.110.4.1167
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the Enzymes of Fructan Biosynthesis in Tubers of Helianthus tuberosus Colombia (II. Purification of Sucrose:Sucrose 1-Fructosyltransferase and Reconstitution of Fructan Synthesis in Vitro with Purified Sucrose:Sucrose 1-Fructosyltransferase and Fructan:Fructan 1-Fructosyltransferase)

Abstract: Sucrosesucrose 1 -fructosyltransferase (1 -SST), an enzyme involved in fructan biosynthesis, was purified to homogeneity from tubers of Helianfbus fuberosus that were harvested in the accumulation phase. Cel filtration under native conditions predicted a molecular mass of about 67 kD. Electrophoresis or gel filtration under denaturing conditions yielded a 27-and a 55-kD fragment. 1 -SST preferentially catalyzed the conversion of sucrose into the trisaccharide 1 -kestose (CF,). Other reactions catalyzed by 1 -S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 15 publications
7
75
0
1
Order By: Relevance
“…A stimulating effect of pyridoxaI-HCI on fructosyltransferases was also observed by other authors (Koops and Jonker, 1996;Simmen etal., 1993;Wagner and Wiemken, 1986).…”
Section: Discussionsupporting
confidence: 84%
“…A stimulating effect of pyridoxaI-HCI on fructosyltransferases was also observed by other authors (Koops and Jonker, 1996;Simmen etal., 1993;Wagner and Wiemken, 1986).…”
Section: Discussionsupporting
confidence: 84%
“…As the sole substrate, 1-kestose cannot be used by the 6-SFT, but is the preferred substrate of the 1-FFT, producing sucrose, nystose (1,1 kestotetraose) and higher DP inulins. Incubation of 1-kestose with purified 1-SST from Asteraceae yielded small amounts of nystose and significant amounts of sucrose and fructose (Koops & Jonker, 1996 ;Lu$ scher et al, 1996 ;Van den Ende et al, 1996). Therefore, analysis of product formation combined with the F : G ratio clearly distinguishes 1-SST from 6-SFT and FFT activities.…”
Section: mentioning
confidence: 99%
“…Incubation of the first 1-SST form (sections 8-10) with 1-kestose showed that the enzyme also acts as an exohydrolase (Figs 1b, 2), producing fructose as described for the 1-SSTs purified from Asteraceae (Koops & Jonker, 1996 ;Lu$ scher et al, 1996 ;Van den Ende et al, 1996). The sucrose generated is then used as a substrate by the 1-SST to produce 1-kestose, as indicated by the glucose production in the assays (Fig.…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations